Building Harmony in Diversity: Pesantren Strategies to Resolve Cultural Conflicts in Non-Muslim Communities - Rintan Arikda Dwi Afida; Siti Aimah; Bannaga Taha Elzubair Hussen (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2024)
This study analyzes pesantren strategies for managing cultural conflicts in non-Muslim communities. Using a qualitative approach with a case study method, data were collected through interviews, observations, and documentation, then analyzed using an interactive model, including data reduction, data presentation, data depiction, and conclusion drawing. The results showed that the pesantren implemented various strategies, such as intercultural dialogue, joint social activities, synergy in religious social activities, collaboration with government agencies, and image enhancement through achievements. These strategies play a significant role in preventing and resolving cultural conflicts, as well as building harmonious relationships with the surrounding community. This research reveals that pesantren not only function as religious education institutions, but also as social agents that contribute to intercultural integration and harmony, especially in plural societies. This finding confirms the important role of pesantren in promoting cross-cultural dialogue and collaboration to create more inclusive and harmonious relationships in non-Muslim communities.